The Effects of the Use of Jire Collaborative Learning Model on Student Learning Outcomes - Moh. Sahyan A. Mile; Mursalin Mursalin; Nova Elysia Ntobuo (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to determine the effect of the use of collaborative learning models on student learning outcomes. This research is true experimental research. The design used is Pretest-Posttest Control Group Design. The sampling technique in this study uses cluster random sampling. This design involves two groups: the experimental group, namely class XI MIPA I, and the control group, namely class XI MIPA II. The instrument used in data collection is an objective learning outcome test. The results of the analysis of hypothesis testing for the experimental and control class show that the experimental and control class t count is > t table for level = 0.05. The average obtained in the experimental class is 91.61 and in the control class, 83.17. It is also supported by the N-gain value obtained for the experimental class which is 0.84 (high) while that obtained for the control class is 0.59 (medium). This concludes that there is an effect of the Jire collaborative learning model on student learning outcomes.